The Urgent Need for an Economics of “Hategoatism” - Steven Payson (Global Labor Organization (GLO), 2019)
The word “scapegoat” is defined as “a person made to bear the blame for others,” and similarly, “scapegoatism” refers to “the act or practice of assigning blame or failure to another, as to deflect attention or responsibility away from oneself” (Collins English Dictionary and Dictionary.com, respectively.) While these definitions do not mention economics specifically, in most cases the blame on the scapegoat is economic in nature. Scapegoatism also provides a convenient, though extremely inferior, substitute for valid analyses of economic problems. Scapegoatism, however, has a partner, dehumanization, which is the process of demonizing certain people as less than human and unworthy of humane treatment. Scapegoatism is not only accompanied by dehumanization, but it is often motivated by it. Thus, “scapegoatism” is a euphemism and it is understudied as a result, because there is no single term of art that combines scapegoatism and dehumanization. This paper offers a solution to this semantic dilemma by proposing the new term, “HATEGOATISM,” for the simultaneous existence of scapegoatism and dehumanization. Only one subfield of economics regularly embraces hategoatism, which is Libertarianism (where the “HATEGOAT” is government workers). Economists must lead by example by combating hategoatism, and that requires cleaning their own house first.
Keywords: B25; B53; D72; D73; H11; H12; I18; I28; I38; J16; J17; J45; J71; P16; P17; Z13; 330; scapegoat; Libertarianism; hate; discrimination; prejudice; government; ethics; economics; labor; blame; fairness; responsibility; economists; demonization; dehumanization